Astroglial CD38 impairs hippocampal synaptic plasticity after global cerebral ischemia - Burch, Amelia M.; Haas, Ami; Orfila, James E.; Tiemeier, Erika; Gamboa, Cassidy De Anda; Chalmers, Nicholas; Quillinan, Nidia; Herson, Paco S. (Frontiers in Stroke, 2024)
Cardiac arrest-induced global cerebral ischemia (GCI) results in profound cognitive impairment in survivors. Our prior work demonstrated persistent disruption of long-term potentiation (LTP) in hippocampal CA1 neurons, correlating with learning and memory deficits in a rodent model of cardiac arrest/cardiopulmonary resuscitation (CA/CPR). Delayed inhibition of the Ca2+-permeable TRPM2 ion channel restored LTP post-CA/CPR, yet the mechanisms upstream of TRPM2 activation remain elusive. This study investigates CD38 as a potential regulator of TRPM2, highlighting a novel target to reverse hippocampal synaptic plasticity deficits after ischemia. We observe elevated levels of CD38 in activated astrocytes in the CA1 region of the hippocampus 7 days following CA/CPR in both male and female mice. Delayed inhibition of CD38 reverses hippocampal synaptic plasticity impairments at subacute timepoints after CA/CPR, phenocopying TRPM2 restoration of LTP. Our previous findings demonstrated that TRPM2 inhibition reverses the CA/CPR-induced enhancement of GABAA receptor (GABAAR) clustering, which contribute to ongoing LTP deficits. We, therefore, assessed the effect of CD38 on GABAergic inhibitory potentiation and find that inhibition of CD38 reverses GABAAR clustering in a TRPM2-dependent manner. In this study, we identify astroglial CD38 as a potential target and upstream regulator of the TRPM2 channel, offering a promising approach to restore hippocampal synaptic plasticity impairments following GCI through modulation of GABAergic signaling.